Analysis Of Factors Determining The Welfare Scores Of Families Receiving Pkh: A Case Study Of Simpang Dolok Village, Datuk Lima Puluh District, Batu Bara Regency - Sitorus, Ade Maharani; Faried, Annisa Ilmi; Hasanah, Uswatun (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the factors that influence the welfare score of Family Hope Program (PKH) recipient families in Simpang Dolok Village, Datuk Lima Puluh District, Batu Bara Regency. Despite PKH implementation to reduce poverty, variations in welfare levels among recipient families persist. This research utilizes Data Tunggal Sosial Ekonomi Nasional (DTSEN) from January 2025 period with a census approach covering all 94 PKH recipient families. Variables analyzed include household head demographic characteristics, family characteristics, household economic conditions, housing conditions, and access to basic services. Multiple linear regression with Ordinary Least Squares (OLS) method was employed for data analysis. The results show that education level of household head, land area controlled, livestock ownership, house floor area, building material quality, and road access conditions have positive and significant effects on DTSEN welfare score. Conversely, number of family members, dependency ratio, and distance to health facilities have negative and significant effects. These findings indicate that improving the welfare of PKH recipient families depends not only on cash transfers but also on enhancing human capital, productive asset ownership, housing quality improvement, and access to basic services.